2019
DOI: 10.1159/000495306
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Google Trends Terms Reporting Rhinitis and Ragweed Pollen Season in Ukraine

Abstract: Background: Google Trends (GT) may represent a new approach to assessing pollen allergy. However, the development of a pan-European sentinel network has raised a problem of translating terms in different languages. A precise definition of the pollen season onset is crucial for the confirmation of a pollen allergy diagnosis and personalized treatment. Ragweed pollen allergy was investigated due to its high allergenicity and wide expansion in Europe. Objectives: The study aimed to examine translations of “ragwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…The query statistics for "hay fever" were assessed by the Cyrillic equivalent of "runny nose". 8 The peaks for "hay fever" and "pollen" were lower than those for "asthma". Thus, Ukraine had the "D" pattern.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The query statistics for "hay fever" were assessed by the Cyrillic equivalent of "runny nose". 8 The peaks for "hay fever" and "pollen" were lower than those for "asthma". Thus, Ukraine had the "D" pattern.…”
Section: Resultsmentioning
confidence: 95%
“…Our previous study showed that Ukrainian Google users apply the GT query "runny nose" ("nasmork" in Cyrillic) as "hay fever". 8 Recent investigations showed that Ukrainian users apply the GT query "travy" (in Cyrillic) as "grass". Thus, in further analysis, this Cyrillic equivalent was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 73 ] The term “ragweed” is mostly used in native languages whereas the direct translations by GTs are sometimes incorrect. [ 75 ] The “ragweed” queries were also visible during spring and summer, indicating that the tree and grass pollen allergy in spring may be perceived as “ragweed.” As a result, the ragweed season found by GTs is far longer than the measured pollen season. [ 76 ]…”
Section: Estimation Of the Pollen Seasonmentioning
confidence: 99%